2015
DOI: 10.1590/s1984-29612015014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Kato-Katz and spontaneous sedimentation methods for the diagnosis of platynosomiasis in Neotropical primates

Abstract: Platynosomiasis is a parasitic infection reported in non-human primates, including marmosets, and is frequently difficult to diagnose. In this study, the Kato-Katz method and the spontaneous sedimentation method were evaluated for their usefulness in identifying Platynosomum eggs in fecal samples from Callithrix penicillata that naturally harbor Platynosomum illiciens. Spontaneous sedimentation allowed the diagnosis of 41.7% (5/12) and 66.7% (8/12) of infected marmosets from one and three slides, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The laboratory diagnosis of platynosomiasis through coproparasitological examination is an important tool in veterinary clinical practice. Methods of sedimentation or flotation in a saturated solution of sugar, salt or zinc are used and although there is not still consensus as to the most suitable method for the recovery Platynosomum eggs in feline feces, some methods have a sensitivity of up to 100% (MATI et al, 2015;RAMOS et al, 2016). The objective of this study was to verify the occurrence of P. illiciens infection in domestic cats in the city of Araguaína, Tocantins, Brazil, using necropsy and coproparasitological tests.…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory diagnosis of platynosomiasis through coproparasitological examination is an important tool in veterinary clinical practice. Methods of sedimentation or flotation in a saturated solution of sugar, salt or zinc are used and although there is not still consensus as to the most suitable method for the recovery Platynosomum eggs in feline feces, some methods have a sensitivity of up to 100% (MATI et al, 2015;RAMOS et al, 2016). The objective of this study was to verify the occurrence of P. illiciens infection in domestic cats in the city of Araguaína, Tocantins, Brazil, using necropsy and coproparasitological tests.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great importance of platynosomosis, mainly in veterinary practice with domestic cats, and recent studies on some aspects related to the life cycle of Platynosomum (Pinto et al, 2014, the diagnosis (Azevedo et al, 2013;Rocha et al, 2014;Mati et al, 2015) and pathology of this infection (including its carcinogenic potential) (Andrade et al, 2012;Daniel et al, 2012;Headley et al, 2012;Montserin et al, 2013), aspects of parasite development and the host-parasite interaction are not completely understood. The scarcity of experimental studies on http://dx.doi.org/10.1016/j.vetpar.2015.04.021 0304-4017/© 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…In this study also reported the same result with the previous study (p-value = 0.478) but there was intensity difference of Ascaris lumbricoides between two groups before and after treatment (p-value = 0.001). However, Payne et al reported a decreasing Ascaris lumbricoides infection after giving 400 mg albendazole and 200,000 IU vitamin A at three months follow up [15][16][17]. The different results should be affected by others factor which influenced the reinfections and drug pharmacology.…”
Section: Discussionmentioning
confidence: 99%